Identifikasi kinematika partikel air dan karakterisasi gelombang ombak dengan metode video tracker - Jamiatul Akmal; An Nisa Magnolia; Ahmad Suudi; Novri Tanti; Asnawi Lubis (Jurnal Teknik Mesin Indonesia, 2023)
As an archipelagic country, Indonesia has great potential for marine resources. This potential must be supported by theoretical studies as the basis for the development of marine technology. For this reason, in this study a laboratory scale wave medium was created as a medium for observing the kinematics of water particles and defining the equations of wave motion. Water particles are represented by buoy balls that are installed at various depth levels. The motion of the buoys is recorded with a video recorder and then converted into a displacement graph with a video tracker application. The wave generator is designed to get a variety of wave sizes and types. The wave generator moves back and forth and is connected to an eccentric rotor by a sliding crank mechanism. The eccentricity of the rotor can be varied, in this study it was determined that e1=3cm, e2=5cm and e3=8cm. From the test results it can be concluded that for e1 the type of wave that occurs is in accordance with the Airy Equation, while for e2 and e3 the waves are obtained in accordance with the Stokes Equation. In addition, it is also known that the displacement of water particle movement is maximum on the surface and decreases at deeper levels.